Instrumento para identificação de fatores de risco e proteção à retinopatia da prematuridade em UTI neonatal - Lopes, Juliana de Fátima (2014)
The Neonatal ICUs are designed for newborns at high risk, as in the case of premature infants.The environment in the NICU is a protective factor for life, but may prove to be inappropriate for the neurological development of preterm, specifically in relation to visual aspects. The aim of this study was to develop and propose a protocol for evaluating the context of the NICU, as a checklist to identify the risk and protective factors visual development of premature infants. Moreover , had the following specific objectives : Map and describe the national and international scientific literature on the Neonatal Intensive Care Units in respect of related visual development of premature variables ; Identify the risk factors and protection to the visual development of premature newborns present in neonatal intensive care units , expressed in the literature. The methodology was based on bibliometric analysis of papers retrieved on the basis of national and international data: VHL, ScienceDirect and Scopus. Bibliometric indicators analyzed under the classification into two categories were produced: Category 1 - Primary Issue (TP) and Category 2 - Issue Secondary (TS). Since the focus of this study lies in the studies classified into Primary Issue , were analyzed and categorized into the following themes : " Retinopathy of Prematurity Risk Factors , Incidence, Prevalence , Screening and Prevention " , " Retinopathy of Prematurity Treatment " , " Normal Development " , " Retinopathy of Prematurity Instrument " , " Environment and Retinopathy of Prematurity " Retinopathy of Prematurity Theory " . These studies the risk factors and protection to the visual development of preterm infants were identified. These factors allowed the construction of check list (initially with partial version and then the final version ). As most of the studies ( 97.7 % ) address on the Retinopathy of Prematurity (ROP) , the instrument will help identify risk and protective for the development of ROP in premature infants in the NICU context factors . It is intended in the future instruments available to professionals in neonatal ICUs, thereby preventing ROP in premature and thereby reduce the incidence and progression of disease.